Carlos Battilana: Professor, Manager, Friend - Pacheco, José (2009)
Anales’ Editorial Committee has lost one of its most renowned staff members. Brilliant professor of our Faculty of Medicine, Carlos Alberto Battilana Guanilo (1945-2009) knew how to transmit knowledge and appeal audiences’ attention, either in young students or not so young contemporary fellows. He got his students interested in the paths of permanent learning and investigation. On the other hand, he committed distinguished physicians and professors to constitute and lead science-friendship interested groups. His vocation in teaching bound him to faculties of medicine and scientific academies and societies, where he coordinated courses and meetings that are pleasantly recalled. His scientific production was devoted to nephrology, immunology, cancer, medical treatment costs. His capacity of management and leadership present since being a student, allowed him to become regional director of a prestigious pharmaceutical laboratory, to organize a faculty of medicine and then to be the dean of the faculty of health sciences of such private university. Carlos was an important element for Anales de la Facultad de Medicina to reach a privileged place among Peruvian biomedical journals. In this biographical sketch we try to summarize Carlos Battilana’s brilliant career, weeks after his departure with no return.